EFFICIENCY OF BORAGE SEEDS OIL AGAINST GAMMA IRRADIATION-INDUCED HEPATOTOXICITY IN MALE RATS: POSSIBLE ANTIOXIDANT ACTIVITY - Khattab, Hala A.H.; Abdallah, Inas Z.A.; Yousef, Fatimah M.; Huwait, Etimad A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Borage (Borago officinal L.) is an annual herbaceous plant of great interest because its oil contains a high percentage of -linolenic acid (GLA). The present work was carried out to detect fatty acids composition of the oil extracted from borage seeds (BO) and its potential effectiveness against γ-irradiation- induced hepatotoxicity in male rats. Materials and Methods: GC-MS analysis of fatty acids methyl esters of BO was performed to identify fatty acids composition. Sixty rats were divided into five groups (12 rats each): Control, irradiated; rats were exposed to (6.5 Gy) of whole body γ-radiation, BO (50 mg/kg b.wt), irradiated BO post-treated and irradiated BO prepost-treated. Six rats from each group were sacrificed at two time intervals 7 and 15 days post-irradiation. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma glutamyl transferase (GGT) levels, lipids profile, as well as serum and hepatic reduced glutathione (GSH) and lipid peroxide (malondialdehyde) (MDA) levels were assessed. Histopathological examination of liver sections were also carried out. Results: The results showed that the high contents of BO extracted by cold pressing, were linoleic acid (34.23%) and GLA (24.79%). Also, oral administration of BO significantly improved serum levels of liver enzymes, lipids profile, as well as serum and hepatic GSH and MDA levels (p<0.001) as compared with irradiated rats after 15 days post irradiation. Moreover, it exerted marked amelioration against irradiation-induced histopathological changes in liver tissues. The improvement was more pronounced in irradiated BO prepost-treated group than irradiated BO post-treated. Conclusion: BO has a beneficial role in reducing hepatotoxicity and oxidative stress induced by radiation exposure. Therefore, BO may be used as a beneficial supplement for patients during radiotherapy treatment.